Assessing the Resource Base of Japanese and U.S. Auto Producers: A Stochastic Frontier Production Function Approach - Lieberman, Marvin B.; Dhawan, Rajeev (Management Science, 2005)
The “resource-based view of the firm” has become an important conceptual framework in strategic management but has been widely criticized for lack of an empirical base. To address this deficit, we utilize a new method for identifying interfirm differences in efficiency within the context of stochastic frontier production functions. Using data on Japanese and U.S. automobile manufacturers, we develop measures of resources and capabilities and test for linkages with firm performance. The results show the influence of manufacturing proficiency and scale economies at the firm and plant level. We apply the parameter estimates to account for Toyota’s superior efficiency relative to other producers.